The Hippo Signaling Core Components YAP and TAZ as New Prognostic Factors in Lung Cancer - Jiang, Yu; Xie, Wen-Jing; Chen, Rong-Wei; You, Wei-Wei; Ye, Wei-Lin; Chen, Hong; Chen, Wen-Xu; Xu, Jian-Ping (Frontiers in Surgery, 2022)
Background: The Hippo pathway is an important signaling cascade in regulating cell and organ growth. However, expressions of Hippo signaling core component YAP and TAZ in lung cancer, especially in small-cell lung cancer(SCLC), and prognosis of them with SCLC remain controversial. Methods: We screened the relevant article and identified eligible study in Pubmed, EMBASE, COCHRANE, and WanFang database, and the combined analysis was performed to investigate the expressions of the major effector YAP and TAZ in lung cancer and its subsets, and the prognostic role of them in lung cancer, especially in SCLC. Results: According to the inclusion and exclusion criteria, a total of six eligible studies related to TAZ and thirteen studies concerning to YAP were enrolled in this meta-analysis. We found that high TAZ was significantly associated with poor overall survival (OS) of non-small cell lung caner (NSCLC) patients in overall population [Ph<0.001, crude hazards ratio (HR)=1.629, 95% confidence interval (CI)=1.199-2.214 for TAZ expression, Ph=0.029, adjusted HR=2.127, 95% CI=1.307-3.460 for TAZ], and Caucasian (Ph=0.043, crude HR=1.233, 95% CI=1.030-1.477 for TAZ expression) as well as Asian population (Ph=0.551, adjusted HR=2.676, 95% CI=1.798-3.982 for TAZ). Moreover, there was a significant negative association between YAP expression and unsatisfactory survival of lung cancer patients(Ph=0.327, crude HR=1.652, 95% CI=1.211-2.253 for YAP expression) and NSCLC patients (DFS: Ph=0.693, crude HR=2.562, 95% CI=1.876-3.499 for YAP expression; Ph=0.920, crude HR=2.617, 95% CI=1.690-4.052 for YAP-mRNA; OS: Ph=0.878, crude HR=1.777, 95% CI=1.233-2.562 for YAP expression), especially in Asian population (Ph=0.414, crude HR=2.515, 95% CI=1.755-3.063 for DFS; Ph=0.712, crude HR=1.772, 95% CI=1.214-2.587 for for OS), however, no association of them was observed in multivariate combined analysis. In Asian population, YAP expression was significantly associated with short OS in combined analysis in Asian population in multivariate data (Ph=0.289, crude HR=4.482, 95% CI= 2.182-9.209) not crude data (Ph=0.033, crude HR=1.654, 95% CI=0.434-6.300 for for OS) . Conclusions: The Hippo pathway is involved in carcinogenesis and progression of NSCLC and SCLC, and high expression of YAP and TAZ are independent and novel prognostic factors for lung cancer.